Analysis of a Four-Firm Competition Based on a Generalized Bounded Rationality and Different Mechanisms - S. S. Askar; A. Al-khedhairi (Complexity)
In this paper, the Caputo derivative with fractional orders is suggested to model a competition among four competing firms. The proposed economic model that describes this competition is constructed based on a generalization of the traditional bounded rationality. In this generalization, we study the influence of memory parameter on the complex behavior of the model. Memory means that we not only take into account the changes in quantities at a current time, but also study the changes occurring in the quantities during an interval of time. For simplicity, it is assumed that the degree of memory is described by one parameter during that interval. The properties of the proposed model such as stability of equilibria, bifurcation, and chaos are studied. Furthermore, we introduce and study the cooperation that may take place among the four firms using Keeney-Raiffa approach.